Catalogue of Vietnamese springtails (Hexapoda, Collembola) - Nguyen, Anh T. T.; Thuy, Kim N.; Arbea, Javier I. (Zootaxa, 2022)
Based on what we believe is a complete survey of the previous literature, the citations of the collembola found in Vietnam are recorded. In total, the catalogue includes 350 species in 118 genera from 21families (69 dubious records). For each species the current name is indicated, as well as the basionym and main synonyms with the complete bibliographic reference, the records for different provinces and regions with the authorships, and the general distribution data. When necessary, taxonomic notes are added. The catalog includes 120 bibliographic references (up to December 2021). The main goal of this paper is to promote future studies on the collembolan fauna of Vietnam.